RT-QuIC optimization for prion detection in soils - Madeline K. Grunklee; Stuart S. Lichtenberg; Gage Rowden; Diana L. Karwan; E. Anu Li; Marc D. Schwabenlander; Tiffany M. Wolf (MethodsX, 2025)
Chronic wasting disease (CWD) is a transmissible neurodegenerative prion disorder affecting cervid species, such as deer, characterized by neurological decline and death. CWD prions (PrPSc) are shed into the environment through excreta, secreta, and carcass decomposition, where they persist for at least 16 years. Detecting prions in environmental matrices, like soil, is challenging as multifaceted interactions between prions and soil components can complicate laboratory assay interpretation. To address these challenges, we conducted a series of experiments on Minnesota native soils to optimize the real-time quaking-induced conversion (RT-QuIC) in vitro prion amplification assay for detection: • We performed negative control experiments to optimize a soil extraction protocol to discern true prion seeding activity from false seeding triggered by native soil characteristics. • We conducted soil spiking experiments to validate RT-QuIC for reliable prion detection. • We performed multiple statistical evaluations and assessments of these control experiments to enhance assay specificity and sensitivity.From these experiments, we identified maxpoint ratio (MPR) as the most effective metric to evaluate true PrPSc detections from background noise in Minnesota native soils. The steps taken to optimize RT-QuIC for Minnesota soils have application for the validation of RT-QuIC for prion detection in other soil types.